Diagnosis and project of structural underpinning of Tampieri Palace - Zanni, Enrique Santiago; Capdevila, Julio Alfredo (Revista ALCONPAT, 2024)
The diagnosis and structural underpinning of the Tampieri Palace is detailed, within a comprehensive restoration project. The building has a high patrimonial value, constituting one of the two existing palaces in the Province of Córdoba, Argentina. It presents fractures in load-bearing masonry, caused by differential settlements, as it is founded on collapsible silts affected by cyclical variations in the water table. The methodology consisted of relieving the existing injuries, conducting searches and technical and historical investigation of its construction to diagnose its structural and constructive state. The intervention was divided into two stages: A) stabilize and seal the building, and B) rehabilitate and restore facades and interiors. It is concluded that the driven micropiles constitute a valid alternative to refund buildings in saturated soils, with minimally destructive interventions.